(-)-Pseudodistomin E: First asymmetric synthesis and absolute configuration assignment - Davies, S; Fletcher, A; Roberts, P; Thomson, J; Zimmer, D (American Chemical Society, 2017)
(-)-Pseudodistomin E has been prepared for the first time, allowing its structure and absolute configuration to be confirmed. The established conjugate addition of lithium (S)-N-allyl-N-(α-methyl-p-methoxybenzyl)amide to methyl (E,E)-hepta-2,5-dienoate generated the C(2)-stereocenter, and iodolactonisation of a derivative generated the remaining two stereogenic centers. Ensuing iodide displacement was achieved using a tethering strategy, to introduce the nitrogen atom to C(5). Decarboxylative coupling of a carboxylic acid with a dialkylzinc reagent completed construction of the tridecadienyl chain.